2018
DOI: 10.1128/msphere.00253-18
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Molecular Serology of HumanChlamydia trachomatisInfections by Peptide Enzyme-Linked Immunosorbent Assays

Abstract: For detection of anti-Chlamydia trachomatis antibodies by serological assays, use of classical whole-organism chlamydial antigens results in high cross-reactivity. These antigens bind mainly antibodies against the major outer membrane protein (OmpA) and bind antibodies against other immunodominant non-OmpA proteins to a lesser extent, resulting in poor assay sensitivity. The specificity of C. trachomatis serology is also compromised by the high prevalence of cross-reactive anti-C. pneumoniae antibodies in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(54 citation statements)
references
References 72 publications
(141 reference statements)
1
52
1
Order By: Relevance
“…Previously, we identified highly reactive and specific B-cell epitopes of immunodominant proteins of all Chlamydia species ( 16 21 ). An important finding was that 16- to 30-amino-acid peptide antigens combined with an N-terminal hydrophilic serine-glycine-serine-glycine spacer were required for optimal signal strength ( 16 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we identified highly reactive and specific B-cell epitopes of immunodominant proteins of all Chlamydia species ( 16 21 ). An important finding was that 16- to 30-amino-acid peptide antigens combined with an N-terminal hydrophilic serine-glycine-serine-glycine spacer were required for optimal signal strength ( 16 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further testing of predicted peptide antigens with sera from C. trachomatis - infected women revealed additional human host-specific C. trachomatis B-cell epitopes that were recognized only by the natural human host ( 20 ) but did not react with sera from mice that were hyperimmunized to C. trachomatis ( 16 ). Subsequently, we comprehensively evaluated the utility of 11 top-ranked peptide antigens from 8 C. trachomatis proteins for use in human C. trachomatis serology ( 21 ). Results obtained for detection of antibodies against 4 commercial anti- C. trachomatis ELISA antigens and these 11 C. trachomatis peptide antigens showed that the peptide assays outperformed any of these commercial ELISAs both in specificity and sensitivity ( 21 ), a consequence of optimal peptide antigen design and ELISA protocol ( 16 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations